Assessment of the Enrichment of Heavy Metals in Coal and Its Combustion Residues - Altıkulaç, Aydan; Turhan, Şeref; Kurnaz, Aslı; Gören, Elif; Duran, Celalettin; Hançerlioğulları, Aybaba; Uğur, Fatma Aysun (American Chemical Society (ACS), 2022)
Coal-fired thermal power plants remain one of the main sources of electricity generation in Turkey. Combustion of coal creates coal ash and slag, which are often stored in landfills located near residential and agricultural fields, increasing the potential for high environmental contamination and health risks. This study investigates the content and enrichment factor (EF) of heavy metals in pulverized lignite coal and its combustion residues from the Kangal lignite coal-fired thermal power plant situated in the Central Anatolian Region of Turkey. The concentration of heavy metals (Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Sr, Zr, Cd, Hg, and Pb) in lignite coal, slag, and fly ash samples were analyzed using an energy dispersive X-ray fluorescence technique. The concentration of Fe is highest while Hg concentration is lowest in the samples. The concentrations of heavy metals are higher in slag and fly ash samples than in lignite coal. Average values of EF (related to Earth's crust average) revealed that extreme enrichment has been shown by arsenic and mercury in lignite coal and fly ash samples while very high enrichment has been shown in slag samples.
Keywords: Chemistry; QD1-999; 13. Climate action; 7. Clean energy